PERBEDAAN PERSEPSI PENANGANAN PADA SITUS CANDl AGUNG DAN TABANIO Dl KALIMANTAN SELATAN - Atmojo, Bambang Sakti Wiku (Balai Arkeologi Kalimantan Selatan, 2008)
There are many choices how to use and manage an archaeological site, for examples: for research purpose, just restore it for future generations or exploit the site for tourism destination. These can be managed either by government or private authority/NGO. In Candi Agung and Tabanio cases -both in Sothern Kalimantan-various interests from different authorities have caused conflict because each authority would like to manage the site according to their own interest. I am of the opinion that one important solution to minimize the negative effects is by practicing coordination between stakeholders. When this is practiced, the archaeological site will be better preserved, while other community activities also continue.